The level of social skills among university students and its impact on their psychological solidity and adaptive behavior - Abu-Alkeshek, Esra’a Omar; Al-Hawamdeh, Basma Mohammad; Zureigat, Haitham Mohammad Ali (International Journal of Evaluation and Research in Education (IJERE), 2025)
Positive social behavior is one of the most important characteristics of humans on this planet. Through these behaviors, the individual shows his sympathy for others and his desire to help them. Therefore, the current study aimed to know the level of social skills among university students and their impact on their psychological solidity and adaptive behavior. To achieve the study objectives, the descriptive analytical approach was used in its implementation. The scale of positive social behavior, psychological solidity, and adaptive behavior was applied to a random sample of 370 male and female students from private universities in Jordan. The study concluded that the level of positive social behavior among students reached 3.49, which is within the average level, and that female students enjoy a high level of social skills compared to university students. The results also indicated a statistically significant effect of the level of social skills on both psychological solidity and adaptive behavior among university students. Positive social behavior also works to provide support between individuals in cases that require support or in difficult situations, which increases their psychological solidity and adaptive behavior. This confirms the effective role of social behaviors in improving both the level of psychological solidity and adaptive behavior among university students.